2016
DOI: 10.1589/jpts.28.3236
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a powered ankle foot orthosis on walking in a stroke subject: a case study

Abstract: [Purpose] Standing and walking are impaired in stroke patients. Therefore, assisted devices are required to restore their walking abilities. The ankle foot orthosis with an external powered source is a new type of orthosis. The aim of this study was to evaluate the performance of a powered ankle foot orthosis compared with unpowered orthoses in a stroke patient. [Subjects and Methods] A single stroke subject participated in this study. The subject was fitted with three types of ankle foot orthosis (powered, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Two studies [35,37] explored a more compliant orthotic system by employing a dynamic AFO. From the fulltext article analysis, it was verified that the selected studies with active orthotic devices [7,8,[39][40][41][42][43] did not accomplish randomized trials. As these studies did not meet the seventh eligibility criterium, they were not included in the systematic analysis.…”
Section: Methodologic Quality Assessmentmentioning
confidence: 99%
“…Two studies [35,37] explored a more compliant orthotic system by employing a dynamic AFO. From the fulltext article analysis, it was verified that the selected studies with active orthotic devices [7,8,[39][40][41][42][43] did not accomplish randomized trials. As these studies did not meet the seventh eligibility criterium, they were not included in the systematic analysis.…”
Section: Methodologic Quality Assessmentmentioning
confidence: 99%
“…Additionally, walking stability can be improved by AFOs. Pourghasem et al 44 tested three types of rehabilitation devices (powered, posterior leg spring, and carbon AFOs) and found that the powered AFO enhances standing and walking abilities of stroke patients most. Additionally, walking with 2-degree-of-freedom (DOF) AFOs has higher stability than with 1-DOF ones.…”
Section: Medical Functionsmentioning
confidence: 99%
“…SEAs 44,52,70,93,94 are commonly configured in motor-based power transmission systems. They transform motor rotations into spring deflections.…”
Section: Design Factorsmentioning
confidence: 99%
“…In contrast to these devices, powered orthoses and exoskeletons are able to provide active assistance to joints, more effectively restoring motion and functional gait [31]. The design and efficacy of exoskeletons and powered orthoses are typically evaluated based on the improvement to kinematics and temporospatial parameters of gait [11,27,43]. However, as these devices have active components, they are inherently heavier than their passive counterparts, and therefore, this additional mass is expected to have some adverse effect on kinetics during walking [25,28].…”
Section: Introductionmentioning
confidence: 99%